Assessment and non-sexist language: TFG rubrics in state universities in Madrid - López Medina, Esteban Francisco (Journal of Learning Styles, 2021)
Recommendations for the non-sexist use of the Spanish language are abundant. In order to find out whether this criterion is effectively considered in the assessment of Final Degree Projects, the study analyses the rubrics of the public universities in the Madrid Region for the degree in Early Childhood Education, as well as the documents referring to their professional competences and the style recommendations of the institutions themselves. The reading of these documents with a gender perspective, together with the questionnaire answered by students of this degree who have submitted the writing of their work to these recommendations, provide the results, which are interpreted in the light of the contributions of language and gender studies together with the educational paradigm of competency-based assessment. These results also suggest future lines of action for the improvement of university assessment rubrics.
Keywords: non-sexist language; Bacherlor's Dissertation; assessment; rubric; competences